Testing The Number of Sprocket Groove on Coconut Fiber Mechanical Peeler - Rafael Gunawan Silaban; Achwil Putra Munir; Riswanti Sigalingging (Jurnal Rekayasa Pangan dan Pertanian, 2013)
This study is aimed at testing the number of sprocket groove on coconut fiber mechanical peeler. The study was conducted to determine the number of sprocket groove to get optimal effectiveness of equipment, the percentage of material that is not peeled and less broken yield and the amount of power needed. The research was conducted at the Laboratory of Faculty of Agriculture, Agricultural engineering, University of North Sumatra in April-June 2012 using the of non-factorial randomized block design using number of sprocket grooves of 27, 29, and 31 pieces. Observed parameters was the effective capacity of the tool, the percentage of material and broken pieces and the amount of  power  needed to strip the coconut husk. The results showed that the number of sprocket groove significantly affected the effective capacity and had no effect on the percentage of defect peeling and broken pieces. The highest effective capacity was obtained on sprocket groove of 27 pieces i.e 537 coconut / hour and the percentage of unpeeled material and broken pieces was 11%. Key words: The number of sprocket groove, coconut fiber peeler.